The Effectiveness Of Art Therapy (Drawing) In Reducing Anxiety: The Role Of A Growth Mindset In Improving Therapeutic Outcomes - Suhartono, Robertus Heru Setyo; Indah Anggreaeni , Anggela Budy (International Journal Labs, 2025)
This study aims to explore the effectiveness of art therapy (drawing) in reducing anxiety and testing the role of growth mindset in improving therapy outcomes. Anxiety was measured using the Hamilton Anxiety Rating Scale (HAM-A), while growth mindset was assessed using the Mindset Assessment Profile (MAP). The study used an experimental design with two groups: an experimental group that followed art therapy (drawing) and a control group that did not receive therapy. The results of the analysis showed a significant decrease in anxiety in the experimental group, with an average decrease of 10 points on the HAM-A scale (p < 0.05). A significant negative correlation was found between an increase in growth mindset and a decrease in anxiety in the experimental group (r = -0.62, p < 0.01). This research shows that art therapy can reduce anxiety, and growth mindset plays an important role in increasing the effectiveness of therapy. These findings recommend the integration of growth mindset in art therapy programs as well as the use of Mind Map Facilitators in deepening self-reflection and healing processes.